Characteristics of Anatomical Structure and Essential Oil Glands of Leaf Peppermint (Mentha Piperita) and Spearmint (Mentha Spicata) - Dwi Octavia, Novi; Pratiwi Puspitawati, Rinie; Bashri, Ahmad (Riviera Publishing, 2023)
Mentha is one of the genera of the Lamiaceae family which can produce essential oils. Mentha species have antioxidant and antimicrobial activity, and the most active compound that plays a role is menthol. This study aimed to analyze the characteristics of variations in the anatomical structure and oil glands of the leaves of two Mentha species as essential oil producers. This type of research was descriptive qualitative in the form of leaf anatomy observations using the fresh and whole mount preparations for longitudinal incisions and the paraffin method for transverse incisions. The research results show that the anatomical structure of the leaves in M. piperita and M. spicata includes the shape, arrangement of epidermal cells and their derivatives, the structure of the tissues that make up the leaves, and variations in glandular and non-glandular trichomes including variations in type, structure, size, and location. The structure of essential oil glands in the leaves of M. piperita and M. spicata species has variations, including number, shape, size, distribution, location, and density. The results of the analysis of the anatomical characteristics of the Mentha species showed that M. piperita had more oil glands than M. spicata. This research has implications for better natural resource management, disaster prevention, and the development of agriculture and fisheries, and this research is the basis for better decision-making by local governments, stakeholders, and related institutions in planning regional development, environmental management, and resource allocation.